Geographical ecology of the symbiotic crabs Libinia ferreirae and Libinia spinosa: Distributional patterns in south and south-eastern coast of Brazil - Gonçalves, Geslaine Rafaela Lemos [UNESP]; Palomares, Luana Ferraz da Silveira [UNESP]; Sousa, Aline Nonato [UNESP]; Stanski, Gilson [UNESP]; Sancinetti, Gustavo [UNESP]; Costa, Rogerio Caetano da [UNESP]; Castilho, Antonio Leão [UNESP] (Wiley, 2020)
The Brazilian coast is home to two species of Majoid crabs: Libinia ferreirae and Libinia spinosa, with similar habits, as they live in symbiosis with the jellyfish Lychnorhiza lucerna during their juvenile stage and dwell on the bottom of the ocean near the coast when adults. This study investigated the spatial and temporal distribution of L. ferreirae and L. spinosa during different ontogenic phases on the south and south-eastern coast of Brazil, between latitudes 22º and 27ºS. Our results showed that both species have different distributions during their development in the three studied regions. Libinia ferreirae were more abundant associated with jellyfish, and L. spinosa were more abundant in the free-living phase. Environmental factors, especially temperature and salinity, for associated and free-living crabs, respectively, are the main factors that need to be supported for the establishment of these specimens. We were able to identify that the presence or absence of hosts (given the ecological interactions between the species) is determinant in finding the associated crabs. Geographical variations (morphology of the regions, marine currents and the strength of the tide) are linked directly to the movement of the jellyfish hosts to the coast, influencing the abundance of L. fereirae and L. spinosa populations and affecting their distribution patterns. We can infer that both species are connected with other populations because of the association with the jellyfish, crabs could be passively transported along the south and south-eastern coast of Brazil, maintaining the connection between metapopulations.
Keywords: ecological interaction; environmental factors; geographical distribution; population connection; symbiosis